Synthesis of Labeled Rifabutin Dithiocarbamate: A Potential Mycobacterium Tuberculosis Imaging Agent - Qaiser Shah Syed; Momin Saima (Journal of Glycomics And Metabolism, 2017)
In this investigation, Rifabutin dithiocarbamate (RFND) was labeled with Technetium-99m (99mTc) using tricarbonyl technique. The labeled RFND was further characterized in terms of radiochemical purity, stability in saline & serum, in vitro bacterial binding, biodistribution in animal model rats and for scintigraphic accuracy in animal model rabbit. Finally different radiobiological characteristics of the 99mTc(CO)3-RFND was compared with the recently reported 99mTc-RFN. It was observed that the dithiocarbamate form of RFN showed better radiochemical purity, stability in saline, bacterial binding, biodistribution and targeted imaging than the recently reported 99mTc-RFN. These better radiobiological parameters posed 99mTc(CO)3-RFND as a more reliable agent for tuberculosis imaging.
Keywords: Rifabutin dithiocarbamate